The Level of Implementation of the Apostle Peter’s Teaching on Marital Harmony Based on 1 Peter 3:8–12 - endas; Sri Wahyuni; Yonathan Purnomo (ORTHOTOMEO : Jurnal Penelitian Ilmiah, 2025)
Marital harmony in Christian families often faces challenges such as differences in perspectives, weak emotional control, and unhealthy communication. These conditions indicate that biblical teachings have not been consistently implemented in family life. Based on this context, this study addresses the question of the level of implementation of the Apostle Peter’s teaching on marital harmony based on 1 Peter 3:8–12 and identifies the most dominant influencing dimension. The purpose of this study is to measure the level of implementation of this teaching and to determine the dominant factor shaping family harmony among the congregation of the Jordan River Church of All Nations in Melawi, West Kalimantan. This study employed a quantitative survey method involving 25 respondents. Data were collected using a validated and reliable questionnaire and analyzed through descriptive statistics, normality tests, confidence intervals, and linear regression analysis. The findings indicate that the implementation level of the Apostle Peter’s teaching is categorized as moderate. All dimensions positively influence marital harmony, with righteous living emerging as the most dominant factor. This study emphasizes the importance of fostering righteous living as a foundation for harmony in Christian family life.